IMPLEMENTASI GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH UNTUK MENINGKATKAN KEDISIPLINAN GURU - Abdurrahman Abdurrahman; Nadila Firdauziyah (Jurnal Manajemen Pendidikan, 2026)
The role of the principal is crucial for the school they lead. Teacher discipline in an educational institution depends on the principal’s leadership style. The purpose of this article is to analyze the leadership style of the principal at SDN Ramban Wetan 4, where there were previously issues with teacher discipline. Consequently, the school faced obstacles in every learning process and was less effective. The implementation of transformational leadership is urgently needed in the institution to resolve teacher discipline issues. This study employs a qualitative approach through data collection, document analysis, observation, and in-depth interviews with staff and the faculty council at SDN Ramban Wetan 4. The research results indicate: first, transformational leadership has a positive effect on teacher discipline; second, leadership and work motivation jointly influence teacher discipline; and third, the appropriate and consistent use of rewards and punishments is a key factor influencing teacher discipline at SDN Ramban Wetan 4. The novelty of this study lies in its focus on the implementation of transformational leadership styles by school principals, which is analyzed not only from a managerial perspective but also in terms of its impact on the sustainable development of a culture of teacher discipline.